2016
DOI: 10.1111/jgs.14718
|View full text |Cite
|
Sign up to set email alerts
|

Is Polypharmacy Associated with Frailty in Older People? Results From the ESTHER Cohort Study

Abstract: OBJECTIVES: To investigate the relationship between polypharmacy and frailty. DESIGN: Longitudinal, observational cohort study. SETTING: Saarland, Germany. PARTICIPANTS: 3,058 community-dwelling adults aged between 57 and 84 years. MEASUREMENTS: Frailty was assessed according to the frailty phenotype, described by Fried et al. Polypharmacy and hyperpolypharmacy were defined as the concomitant use of five or more and 10 or more drugs, respectively. We assessed associations between polypharmacy and prevalent and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
152
5
10

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(193 citation statements)
references
References 26 publications
26
152
5
10
Order By: Relevance
“…Our estimates of the prevalence of polypharmacy and PIMs are relatively high compared to previous estimates [7,9,11,23], which was expected considering our methodology. Indeed, the prevalence of polypharmacy should be considered with regard to our definition that encompasses all the medications prescribed over 3-month periods.…”
Section: Prevalence Of Polypharmacy and Pimssupporting
confidence: 62%
See 1 more Smart Citation
“…Our estimates of the prevalence of polypharmacy and PIMs are relatively high compared to previous estimates [7,9,11,23], which was expected considering our methodology. Indeed, the prevalence of polypharmacy should be considered with regard to our definition that encompasses all the medications prescribed over 3-month periods.…”
Section: Prevalence Of Polypharmacy and Pimssupporting
confidence: 62%
“…Epidemiological studies have shown that frail people are more likely to receive polypharmacy compared to non-frail individuals [7][8][9][10][11]. Polypharmacy exposes old people to various risks [12], notably adverse drugs events [13], falls [14], increased use of healthcare services, and mortality [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…68 Across 1662 men aged who were more than 70 years of age with a follow-up period of 2 years, Gnjidic et al 6 found that the use of more than 5 medications is associated with incident frailty. In a cohort with similar characteristics (n = 1705, follow-up period = 5 years), Jamsen et al 7 found that a higher number of medications was associated with greater risk of mortality in robust community-dwelling older men and with a higher risk of transitioning from the robust state to the prefrail state.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Furthermore, several short-term follow-up studies have suggested that polypharmacy is associated with a higher risk for incident frailty. 68 However, some limitations are evident with these studies, including the relatively short follow-up period (maximum 5 years) and the small sample sizes. The relationship between polypharmacy and frailty is complex; several studies have suggested polypharmacy is associated with frailty, 68 whilst others have suggested that a higher adherence to medications could be associated with lower mortality rate in frail older subjects.…”
mentioning
confidence: 99%
See 1 more Smart Citation